Post-purchase behavior: consume complaint behavior / Azmi Mat...[et al.] - Mat, Azmi; Mohd Ali, Ainunnazlee; Mohamad Salleh, Mohammad Zaim; Kori, Nur Liana (2014)
Consumer complaints are no longer viewed as a negative light to the organization performance. In general, consumer complaints can be used as a benchmark for appraisal of their service quality and an important opportunity for the companies to improve. In other words, complaints play an important indicator to measure the level of service excellent or quality in a product. If there is no complaint from consumers, it is dangerous. It means, consumers do not care at all or they are apathetic towards the services or products offered by the organizations. Hence, consumers should be encouraged to speak up directly to the organization when they experience a service failure as complaints can help companies to be aware of their shortcomings and failures. Therefore, this paper aims to explore the factors affecting consumer complaining behavior as well as to investigate the possible action that consumer will take when they experience a dissatisfaction episode. This study is beneficial for the companies, future researchers and individual consumers as well.